Axilloskopická disekce lymfatických uzlin u nemocných se zhoubnými nádory prsní žlázy - Vokurka, Jiří; Kašpar, Michal; Kábela, Martin; Chrenko, Vojtěch; Paseka, Tomáš; Svobodník, Adam (Iga MZ ČR, 2010)
The development and verification of mini-invasive surgical technique in patients with malignant mammary tumours in the axillary region. The reduction in morbidity and improved cosmetic effect. Statistical evaluation and conclusions for the practice.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: lymfadenektomie; endoskopie; miniinvazivní chirurgické výkony; lymfatické metastázy; nádory prsu; Breast Neoplasms; Lymphatic Metastasis; Minimally Invasive Surgical Procedures; gynekologie a porodnictví; onkologie; Lymph Node Excision; Endoscopy